2015
DOI: 10.1186/s12936-015-0912-z
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito age and avian malaria infection

Abstract: BackgroundThe immune system of many insects wanes dramatically with age, leading to the general prediction that older insects should be more susceptible to infection than their younger counterparts. This prediction is however challenged by numerous studies showing that older insects are more resistant to a range of pathogens. The effect of age on susceptibility to infections is particularly relevant for mosquitoes given their role as vectors of malaria and other diseases. Despite this, the effect of mosquito a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 85 publications
(115 reference statements)
1
30
3
Order By: Relevance
“…Such observations have been made in Diptera, Hymenoptera, Lepidoptera, Coleoptera, and Odonata. Often, senescence refers to a decrease in the potency of a response that involves encapsulation, nodulation or melanization (Daukste et al, 2012; Park et al, 2011; Prasai and Karlsson, 2012; Robb and Forbes, 2006), or refers to a decrease in the number of hemocytes or their phagocytic activity (Hillyer et al, 2005; Horn et al, 2014; Mackenzie et al, 2011; Park et al, 2011; Pigeault et al, 2015; Schmid et al, 2008). This senescence often results in increased infection intensities in older insects, which may be accompanied by either increased (Roberts and Hughes, 2014) or decreased (Hillyer et al, 2005) survival.…”
Section: Insect Age and Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations have been made in Diptera, Hymenoptera, Lepidoptera, Coleoptera, and Odonata. Often, senescence refers to a decrease in the potency of a response that involves encapsulation, nodulation or melanization (Daukste et al, 2012; Park et al, 2011; Prasai and Karlsson, 2012; Robb and Forbes, 2006), or refers to a decrease in the number of hemocytes or their phagocytic activity (Hillyer et al, 2005; Horn et al, 2014; Mackenzie et al, 2011; Park et al, 2011; Pigeault et al, 2015; Schmid et al, 2008). This senescence often results in increased infection intensities in older insects, which may be accompanied by either increased (Roberts and Hughes, 2014) or decreased (Hillyer et al, 2005) survival.…”
Section: Insect Age and Immune Responsesmentioning
confidence: 99%
“…This senescence often results in increased infection intensities in older insects, which may be accompanied by either increased (Roberts and Hughes, 2014) or decreased (Hillyer et al, 2005) survival. Seemingly conflicting with the concept of immunosenescence, reports on insect vectors have demonstrated that older flies are less capable of becoming infected with – and transmitting – malaria parasites, filarial nematodes, or the parasites that cause human African trypanosomiasis (Aksoy et al, 2014; Ariani et al, 2015; Pigeault et al, 2015), indicating that the relationship between immunity, tolerance, and aging is complex.…”
Section: Insect Age and Immune Responsesmentioning
confidence: 99%
“…Besides mosquito and parasite genetic factors, there is a great diversity of ways in which biotic and abiotic external and within‐vector environmental factors (temperature, mosquito diet, insecticide exposure, microbial gut flora, infection history, mosquito age, etc.) can influence with mosquito competence (Alout, Djègbè, et al., ; Gendrin et al., ; Hien et al., ; Lefèvre, Vantaux, Dabiré, Mouline, & Cohuet, ; Murdock, Blanford, Luckhart, & Thomas, ; Murdock, Paaijmans, Cox‐foster, Read, & Thomas, ; Pigeault, Nicot, Gandon, & Rivero, ; Pollitt, Bram, Blanford, Jones, & Read, ; Shapiro, Murdock, Jacobs, Thomas, & Thomas, ; Takken et al., ; Vantaux, Dabiré, Cohuet, & Lefèvre, ). However, it is still unknown whether these environmentally driven changes in competence illustrate mere passive susceptibilities to environmental stresses (nonadaptive plasticity) or active beneficial shifts in either parasite growth and development or mosquito immune responses (parasite or vector adaptive phenotypic plasticity; Box 2).…”
Section: Mosquito Competence (V)mentioning
confidence: 99%
“…First, naïve larvae have more hemocytes than naïve adults (League et al, ). Second, the number of hemocytes in adult mosquitoes declines with age, a phenomenon that contributes to immune senescence (Castillo, Robertson, & Strand, ; Hillyer et al, ; King & Hillyer, ; League et al, ; Pigeault, Nicot, Gandon, & Rivero, ). However, an adult infection results in an increase in the number of hemocytes in some mosquito species but not others (Coggins et al, ; Hillyer et al, ; King & Hillyer, ; League et al, ).…”
Section: Discussionmentioning
confidence: 99%